Sand House Therapy: Health Tourism Innovation Based on Local Wisdom through the Utilization of Sand Mattresses in Sumenep Regency - Oktaviyani, Haniza; As Sauri, Sofyan; Laora, Marisa; Sevtiana, Lily; Huzaimah, Nailiy; Hidayat, Syaifurrahman (Sarana Ilmu Indonesia (salnesia), 2025)
The community empowerment program initiated by the HIMIKA PPK Team of Wiraraja University provided a solution through the development of a Health Tourism Village known as